Med distanciranostjo in angažiranostjo - Jontes, Dejan (Dve domovini, 2017)
The paper analyses reporting about the "refugee crisis" in Slovenia's three main daily newspapers Delo, Dnevnik and Večer in the first weeks of mass migrations through the country that were named "the first and the second wave of refugees" by the journalists. The analysis focuses on the question of framing and on the dominant journalistic conventions through which objectivity is performed. The paper tries to reflect on the paradox in reporting these issues where the problem is dominantly framed in terms of humanitarian crisis on the explicit level and rarely as a security issue but on the connotative level factism and episodic framing suggest another reading of the problem that supports the fear of the imigrants. What is more, examples of more engaged reporting can be found where archetypal figures of heroes are called upon and where daily news functions similar as myth.
Keywords: Begunci; Časniki; Newspapers; Objectivity; Objektivnost; Poročanje; Refugees; Reporting